CONSEQUENCES OF BIRTH INTERVAL ON NEWBORN HEALTH - Zaly, Nedra Wati; Rahardja, Mugia Bayu; Murtiningsih, Murtiningsih; Fadila, Wisnu (Jurnal Biometrika dan Kependudukan, 2024)
Babies with Low Birth Weight (LBW) are more at risk of occurring at short birth intervals than at longer birth intervals. The reproductive capacity of women can decrease and return to the primiparous state in women who experience long birth intervals which can also be risky for the baby. The purpose of this study was to determine the consequences of birth spacing on the health of newborns. This study uses two methods, both quantitative and qualitative. The quantitative method uses data from the 2017 IDHS with a cross-sectional research design. The sample of this research is mothers who gave birth in the last five years and had at least 2 (two) pregnancies. The results of this study found that 9.8% experienced short birth spacing and 7.2% of babies born with low birth weight. This study confirms the existence of a relationship between birth spacing and the incidence of LBW babies. Short birth interval risks giving birth to babies with LBW. It is hoped that the results of this study will become an initial reference for designing policies on birth intervals to improve newborn health and reduce infant mortality.